2006
DOI: 10.1007/s11199-006-9128-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotyping and Under-representation of Female Characters in 200 Popular Children’s Picture Books: A Twenty-first Century Update

Abstract: Gender stereotyping and under-representation of girls and women have been documented in children's picture books in the past, in the hope that improvements would follow. Most researchers have analyzed awardwinning books. We explored sexism in top selling books from 2001 and a 7-year sample of Caldecott award-winning books, for a total of 200 books. There were nearly twice as many male as female title and main characters. Male characters appeared 53% more times in illustrations. Female main characters nurtured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
144
2
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(190 citation statements)
references
References 22 publications
13
144
2
16
Order By: Relevance
“…Past and more recent examinations of print media aimed at children reveal both unequal gender representation and common gender stereotypes. In their study of 200 topselling popular children's books, Hamilton et al (2006) looked at gender representation in pictures, characters, characters' behavior and personality as well as setting and they found out that female characters were under-represented in children's picture books. Another research conducted by Fitzpatrick and McPherson (2010) yielded similar results.…”
Section: B Gender Biasmentioning
confidence: 99%
“…Past and more recent examinations of print media aimed at children reveal both unequal gender representation and common gender stereotypes. In their study of 200 topselling popular children's books, Hamilton et al (2006) looked at gender representation in pictures, characters, characters' behavior and personality as well as setting and they found out that female characters were under-represented in children's picture books. Another research conducted by Fitzpatrick and McPherson (2010) yielded similar results.…”
Section: B Gender Biasmentioning
confidence: 99%
“…In his study on woman characters in pictured child books, Vannicopulou (2004) found that mother has the fundamental responsibility for raising children and acts like a service maid in the house and women are seen indoor or in places where they assume role of mother and housewife alike. Like these findings, Hamilton et al (2006) in their studies argued that female characters deal with child education more than male ones and they are seen more indoor scenes rather than outside. Besides, they found that women contributed less to professional life compared to men and in the pictured books for both children and adults discrimination persisted.…”
Section: Introductionmentioning
confidence: 76%
“…Some researchers (e.g., Dickinson et al, 2012;Sé né chal et al, 1996;Waxman et al, 2014) have looked into the pedagogic values of storybooks with respect to children's cognitive and linguistic development. Others (e.g., Crabb & Marciano, 2011;Hamilton et al, 2006;Stephens, 1992), however, have taken a critical lens and have examined the ideologies which storybooks embody. By nature, the present study will be one of the latter.…”
Section: Introductionmentioning
confidence: 99%